2020
DOI: 10.1590/1980-265x-tce-2020-0392
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Auriculoacupuncture on the Sleep Quality of Working Nursing Professionals During the Covid-19 Pandemic

Abstract: Objective: to evaluate the effectiveness of auriculoacupuncture in improving the sleep quality of nursing professionals in the fight against the COVID-19 pandemic. Method: quasi-experimental before and after study, without a control or matching group performed from May to July 2020, in a referral hospital for infectious diseases in Ceará. The sample consisted of 26 nursing professionals, including nurses and technicians, who performed three sessions of auriculoacupuncture, once a week, for four weeks. Sleep q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
1
7
0
9
Order By: Relevance
“…In a quasi-experimental study carried out with auriculotherapy in health professionals, it was found that the intervention was able to improve the dimensions of subjective sleep quality by more than 50% (p = 0.001), habitual efficiency (p = 0.011), sleep duration and reduced sleep disorders (p < 0.001). This improvement is justified by the possibility of regulating neurotransmitters and hormonal factors involved in the sleep and wakefulness process, with the stimulation of the points (8) . Another aspect is that the practice has already obtained results in the first consultation, which can reinforce its use in the Safe Child ® Method, which provides only on stimulus prior to the procedure.…”
Section: Applying the Safe Child® Methods For Inserting Earrings In C...mentioning
confidence: 99%
See 3 more Smart Citations
“…In a quasi-experimental study carried out with auriculotherapy in health professionals, it was found that the intervention was able to improve the dimensions of subjective sleep quality by more than 50% (p = 0.001), habitual efficiency (p = 0.011), sleep duration and reduced sleep disorders (p < 0.001). This improvement is justified by the possibility of regulating neurotransmitters and hormonal factors involved in the sleep and wakefulness process, with the stimulation of the points (8) . Another aspect is that the practice has already obtained results in the first consultation, which can reinforce its use in the Safe Child ® Method, which provides only on stimulus prior to the procedure.…”
Section: Applying the Safe Child® Methods For Inserting Earrings In C...mentioning
confidence: 99%
“…It is worth reflecting that the studies cited to elucidate the pharmacological and non-pharmacological practices used in the Safe Child ® Method were carried out in procedures that cause severe pain and/or in chronic conditions. Anesthetic ointment (4) , maternal lap, and breastfeeding (5) were used in punctures in well-vascularized and innervated areas; distraction was used in children with cancer, a state in which more than 70% of patients have severe pain during the procedures (6) ; auriculotherapy was performed in the adult population (8) ; and low-intensity laser in chronic conditions (9) ; however, all studies provided positive and significant effects on analgesia, inflammation, sleep, and healing. Thus, the use of these techniques to perforate the earlobe can be a positive predictor of child comfort.…”
Section: Applying the Safe Child® Methods For Inserting Earrings In C...mentioning
confidence: 99%
See 2 more Smart Citations
“…In health professionals, the impacts of the pandemic are enhanced by physical exhaustion, high workload, lack of personal protective equipment, inadequate working conditions, need for ethically complex decisions on care rationing, emotional tensions and severity of the cases 4 . Such occupational demands are frequent causes of stress and insufficient sleep and can contribute to changes in the work process, increasing the risk of accidents 5 .…”
Section: Introductionmentioning
confidence: 99%